Bilingual Education Comes to Kansas - George Hughes (Educational Considerations, 1974)
In some areas as many as 90 per cent of our Mexican-American children will not graduate from high school. They have been scholastically crippled by an educational system which demands they speak two languages fluently while their classmates only have to cope with one.